Trend Analysis of the Financial Statements of PT Kalbe Farma Tbk (KLBF) (2020–2024) - Mia Aida Yuliana; Endarwati Endarwati (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study discusses analyzing financial ratio trends in the form of liquidity, profitability, solvency, and activities at PT Kalbe Farma Tbk during 2020 to 2024. The purpose of the study was to understand the pattern of changes in financial ratios and their implications on the financial performance of companies, given the importance of the pharmaceutical industry after the COVID-19 pandemic occurred. Using a descriptive quantitative approach using secondary data from the company's annual financial statements, trend analysis was carried out using the Least Square method. The results show that PT Kalbe Farma Tbk has good liquidity and activities, but its profitability is still below industry standards and needs attention to its solvency structure. This research is expected to contribute to financial decision-making in the pharmaceutical sector as well as become a reference for investors and academics.